DIFFUSIONS AND BARRIERS OF TECHNOLOGY-AIDED DELIVERY OF ENABLERS IN ELEMENTARY SCHOOLS IN THE DISTRICT OF CUARTERO - Fegarido, Martha Mae B (IDEAS: Journal of Management & Technology, 2024)
Many school districts support technological advances in the classroom by giving gadgets suchas tablets and computers, moving forward web networks, and actualizing programs planned tomove forward with ease of use. The study aimed to determine the level of diffusions andbarriers of technology-aided delivery of enablers in the District of Cuartero for the school year2023-2024. A validated and reliability tested researcher-made questionnaire was used togather the needed data from randomly selected respondents. The statistical tools used toanalyze and interpret data were frequency count, percentage, mean, t- test, analysis ofvariance, and Pearson-r. Findings of the study revealed that the level of diffusions oftechnology-aided delivery of enablers as a whole was very high. The extent of barriers oftechnology-aided delivery of enablers was high. There were no significant differences in thelevel of diffusions of technology-aided delivery of enablers when grouped according to sex,and number of ICT training attended except age and salary were significantly differenceexisted. There were no significant differences in the extent of barriers of technology-aideddelivery of enablers when grouped according to sex, age, and salary except number of ICTtrainings attended which showed significant difference. And the level of diffusions issignificantly related to the extent of barriers of technology-aided delivery of enablers in theDistrict of Cuartero. Teachers need to enrich further their digital competencies for thebetterment and improvement of their teaching process.